2016
DOI: 10.1007/s11274-016-2175-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of chemical constituents, antimicrobial and anticancer activities of dichloromethane extracts of Sordariomycetes sp. endophytic fungi isolated from Strobilanthes crispus

Abstract: Plants are primary source of natural product drugs. However, with every new bioactive molecule reported from a plant source, there follows reports of endangered status or even extinction of a medicinally important plant due to over-harvesting. Hence, the attention turned towards fungi namely the endophytes, which reside within medicinally important plants and thus may have acquired their medicinal properties. Strobilanthes crispus is a traditional medicinal plant which has been used traditionally to treat kidn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 32 publications
0
9
0
1
Order By: Relevance
“…Only pyrrolo [1, 2-a] pyrazine-1, 4-dione, hexahydro-3-(2-methylpropyl) out of the six compounds detected from the extract of Streptomyces sp. DST119 has been previously reported for its antimicrobial activity [ 78 , 79 ]. Two of the seven compounds, carbonic acid, 2,2,2-trichloroethyl undec-10-enyl ester and 1-butanol, 2-methyl-acetate from the extract of Streptomyces flavogriseus DST52 were reported earlier for their antimicrobial activities [ 80 – 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only pyrrolo [1, 2-a] pyrazine-1, 4-dione, hexahydro-3-(2-methylpropyl) out of the six compounds detected from the extract of Streptomyces sp. DST119 has been previously reported for its antimicrobial activity [ 78 , 79 ]. Two of the seven compounds, carbonic acid, 2,2,2-trichloroethyl undec-10-enyl ester and 1-butanol, 2-methyl-acetate from the extract of Streptomyces flavogriseus DST52 were reported earlier for their antimicrobial activities [ 80 – 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Suppression of microbial growth by crude filtrate of endophytes was determined in order to investigate antimicrobial activity of endophytes [49] . Results showed that all isolated endophytes displayed significant inhibition zone against at least one of the tested microbial pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Since an endophyte can produce a complex mixture of compounds, it becomes interesting to extract bioactive compounds using organic solvents in increasing order of polarity ( 21 , 41 ). Overall, microbial metabolites released into the liquid culture medium by the endophytic fungus are often extracted with DCM and EtAc ( 21 , 42 , 43 ). In this study, DCM and EtAc were employed as solvents of lower and higher polarity, respectively, to obtain the secondary metabolite compounds produced by MF31b11.…”
Section: Discussionmentioning
confidence: 99%